Aerospace Engineering - Dekoulis, George (IntechOpen, 2019)
This book is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of engineering. The book comprises chapters authored by various researchers and edited by an expert active in the aerospace engineering research area. All chapters are separate but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on engineering, and opening new possible research paths for further novel developments.